The improvement of node Mobility in RPL to increase transmission efficiency - Pak Satanasaowapak; Chatchai Khunboa (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The Internet of Thing has gained interested to use for daily devices to industrial applications. Mission-critical applications such as connected car and healthcare services require real-time communications and mobility support. The 6LoWPAN protocol and IPv6 Routing Protocol for Low Power and Lossy Networks (RPL) have become the standard for the IoT. However, the RPL protocol is unable to support the application requirement causing from the high network overhead, long message latency and high packet loss rate due to mobility. Thus, in this paper, we propose a new cost metric combining the number of hops, RSSI values, and the summation of delay to enhance RPL mobility. In addition, we define the movement notification for the mobile node to activate mobile detection and parent selection processes. Finally, we presented a comparative study of the improved RPL protocols in terms of packet delivery ratio, end-to-end delay and the number of control messages. The result shows that improved RPL protocol with the new cost metrics provides a high packet delivery ratio and offers a low message latency.